Integrin Activation Enables Sensitive Detection of Functional CD4+ and CD8+ T Cells: Application to Characterize SARS-CoV-2 Immunity - Schöllhorn, Anna; Schuhmacher, Juliane; Besedovsky, Luciana; Fendel, Rolf; Jensen, Anja T. R.; Stevanović, Stefan; Lange, Tanja; Rammensee, Hans-Georg; Born, Jan; Gouttefangeas, Cécile; Dimitrov, Stoyan (Frontiers in Immunology, 2021)
We have previously shown that beta2-integrin conformational change is a very early activation marker that can be detected with fluorescent multimers of its ligand ICAM-1 for a rapid assessment of antigen-specific CD8+ T cells. Here, we describe a modified protocol of this assay for sensitive detection of functional antigen-specific CD4+ T cells using a monoclonal antibody (clone m24) specific for the open, high affinity conformation of the beta2-integrin. Kinetics of beta2-integrin activation were different on CD4+ and CD8+ T cells (several hours vs. few minutes, respectively), however, m24 antibody readily stained both cell types 4-6 hours after antigen stimulation. With this protocol, we were able to monitor ex vivo effector and memory CD4+ and CD8+ T cells specific for SARS-CoV-2, CMV, EBV and HBV in whole blood or cryopreserved PBMCs of infected or vaccinated individuals. By costaining with m24 and CD154 antibodies, we assessed extremely low frequencies of polyfunctional CD4+ T cell responses. Our novel assay thus allows very sensitive and simultaneous screening of both CD4+ and CD8+ T cell reactivities, with versatile applicability in clinical and vaccination studies.